Estimating the seroprevalence of chikungunya virus exposure in Shimoga district, Karnataka state: A hospital‐based study during 2014‐2018. Issue 1 (8th September 2019) - Shilpa, Cheerngod; Kavitha, Karunakaran; Sudheesh, Nittur; Sabeena, Sasidharanpillai; Prasad, Varamballi; Hindol, Maity; Arunkumar, Govindakarnavar
Abstract: Chikungunya fever is a viral disease transmitted to humans by the bite of infected mosquitoes. The disease is characterized by fever, headache, rash, severe joint, and muscle pain. To evaluate the disease burden in the population and the effectiveness of public health measures, periodic seroprevalence surveys are essential. Chikungunya outbreaks were reported from many Asian countries since 2005, after more than three decades of disappearance. The study aimed to estimate the seroprevalence of the chikungunya virus in southern parts of Karnataka state, through demonstrating chikungunya virus‐specific neutralizing antibodies. A cross‐sectional study was carried out using 509 archived blood samples from a hospital‐based acute febrile illness surveillance project, representative of the period between June 2014 and 2018. The study reported a 3.7% seroprevalence of chikungunya virus‐neutralizing antibodies in Thirthahalli and Hosanagara taluks of South Karnataka. The low prevalence of chikungunya‐neutralizing antibodies indicates that a major population is unexposed and prone to future outbreaks. Highlight: This study reports the low prevalence of chikungunya neutralising antibodies among the rural residents of Shimoga district of Karnataka, India indicating large number of susceptible individuals and hence possibility of outbreaks.